Criticism of Maudhu'i's Interpretation of the Term 'Prank' in the Context of the Qur'an - Laili Nabila; Yeti Dahliana; Alfiyatul Azizah; Kharis Nugroho; Andri Nirwana AN (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The prank phenomenon has become a rampant trend among the millennial generation, especially in the realm of social media. Pranks are often thought of as a form of entertainment and humor, but in some cases, the practice can have a negative impact, including harming the other party both physically and psychologically. In Islam, there are limits to joking that emphasize honesty, ethics, and not harming others. This research aims to criticize various academic studies that discuss the phenomenon of prank in the perspective of the Qur'an. Pranks as a social phenomenon that develops in the digital era are often studied from various perspectives, including Qur'anic interpretation, hadith, psychology, and Islamic law. Using the library research method, this study evaluates the weaknesses and advantages of previous studies related to prank, especially in terms of methods, sources of interpretation used, and the relevance of the study in the modern social context. The results of the analysis show that most of the previous research is still limited to certain interpretations, lacks consideration of psychological and sociological aspects, and is minimal in discussing legal regulations related to pranks on social media. This study is expected to provide new insights in examining the phenomenon of pranks more comprehensively, taking into account a broader perspective in Islamic studies and social sciences.